KONSEP PENATAAN PERMUKIMAN KUMUH KELURAHAN KUBU MARAPALAM KECAMATAN PADANG TIMUR KOTA PADANG - Desy Aryanti; Rini Asmariati; Rahmadiansyah; Riri Amrizal (JURNAL REKAYASA, 2021)
Kubu Marapalam is one of the sub-districts located in Padang Timur District in West Sumatera province with a sizeable area of 98 hectares (Ha) and occupied by .886 inhabitants. Based on Padang Mayor Decree Number.163 of 2014, Kubu Marapalam Sub-district is a slum of 1.48 Ha with the number of population is 508 Inhabitants/127 KK. This area is classified as a high density population and rejuvenation of the urban residential environment is required. With a dense population, inappropriate inhabitants’ behavior such as littering, and no green open space as well as open space availability, hence this area is vulnerable for flood. Problem solving with a qualitative descriptive method can produce a concept of restructuring community settlement in a high density and slums occupancy. This restructuring concept is expected to be able to create an appropriate and healthy occupancy with more green space. The purpose of this research is to find out the direction of restructuring concept in the high density and slum area which will be able to improve the quality of a healthy and appropriate settlement environment.